2017
DOI: 10.1186/s12876-017-0717-3
|View full text |Cite
|
Sign up to set email alerts
|

Double-catheter lavage combined with percutaneous flexible endoscopic debridement for infected pancreatic necrosis failed to percutaneous catheter drainage

Abstract: BackgroundInfected pancreatic necrosis (IPN) is a serious local complication of acute pancreatitis, with high mortality. Minimally invasive therapy including percutaneous catheter drainage (PCD) has become the preferred method for IPN instead of traditional open necrosectomy. However, the efficacy of double-catheter lavage in combination with percutaneous flexible endoscopic debridement after PCD failure is unknown compared with surgical necrosectomy.MethodsA total of 27 cases of IPN patients with failure PCD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 26 publications
1
34
0
Order By: Relevance
“…We speculated that these procedures might explain the refractory postoperative pancreatic fistula. In the therapeutic strategy for acute severe pancreatitis, continuous local lavage is currently accepted as an effective treatment option [3437]. In our case, continuous local lavage was performed via a transnasal infusion and a transgastric drainage, with the pancreatic drainage tube placed in a retrograde fashion (Figure 4D).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We speculated that these procedures might explain the refractory postoperative pancreatic fistula. In the therapeutic strategy for acute severe pancreatitis, continuous local lavage is currently accepted as an effective treatment option [3437]. In our case, continuous local lavage was performed via a transnasal infusion and a transgastric drainage, with the pancreatic drainage tube placed in a retrograde fashion (Figure 4D).…”
Section: Discussionmentioning
confidence: 95%
“…Historically, only surgical approaches have been recommended for treating necrotizing and infected pancreatitis [38,39]. Today, however, continuous local lavage is currently accepted as an effective treatment for severely infected pancreatitis [3437]. We suggest that continuous local lavage may have a therapeutic potential even for pancreatic juice-related complications, including postoperative pancreatic fistula.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, continuous positive drainage via a large-bore double-lumen irrigation-suction tube is one of the key techniques. The significance of positive drainage system has been confirmed by several studies [4,13,14]. The procedure of ON consist of a laparotomy through a bilateral subcostal incision, after blunt removal of pancreatic and peri-pancreatic necrosis, several large-bore double-lumen irrigation-suction tube inserted for postoperative CPD (Fig.…”
Section: Treatmentmentioning
confidence: 88%
“…On one hand, 45.4% patients were detected with GI fistula after performing open necrosectomy. DLI, ileostomy or colostomy was performed for 65.3% colonic fistulas [13,14]. On the other hand, with a low threshold for colonic resection due to unreliable detection of ischemia or imminent perforation by outside inspection during surgery for IPN, histologically examined specimens showed that colonic resection was unnecessary in 20-50% [12,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In pancreatitis therapy, minimally-invasive drainage ( e.g ., percutaneous and transluminal approaches) is currently considered useful, especially for necrotizing and infected pancreatitis[5-7]. Recently, continuous local lavage (CLL) has been reevaluated as effective treatment for severe infected pancreatitis[8-11].…”
Section: Introductionmentioning
confidence: 99%